2003
DOI: 10.2174/1389200033336900
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Metabolism and Mechanism of Action: A Review

Abstract: Retinoids are vitamin A (retinol) derivatives essential for normal embryo development and epithelial differentiation. These compounds are also involved in chemoprevention and differentiation therapy of some cancers, with particularly impressive results in the management of acute promyelocytic leukemia (APL). Although highly effective in APL therapy, resistance to retinoic acid (RA) develops rapidly. The causes of this resistance are not completely understood and the following factors have been involved: increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
167
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(170 citation statements)
references
References 58 publications
2
167
0
1
Order By: Relevance
“…Previous studies have reported that all-trans-4-oxo-RA and 13-cis-4-oxo-RA widely exist in human and animal serum (36,37) and can be eliminated from the body through urinary excretion (38). In another study, Li et al also detected the glucuronide conjugate of all-trans-4-oxo-RA and 13-cis-4-oxo-RA in urine of rats that had been fed with all-trans-RA, 9-cis-RA, and 13-cis-RA previously (39).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that all-trans-4-oxo-RA and 13-cis-4-oxo-RA widely exist in human and animal serum (36,37) and can be eliminated from the body through urinary excretion (38). In another study, Li et al also detected the glucuronide conjugate of all-trans-4-oxo-RA and 13-cis-4-oxo-RA in urine of rats that had been fed with all-trans-RA, 9-cis-RA, and 13-cis-RA previously (39).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the above, we found an independent association between RPB4 levels and hepatic lipase activity in patients with type 2 diabetes and in those with CAD. RBP4 is a transporter protein for retinol that serves as a precursor for the synthesis of ligands of the retinoid X receptor and retinoic acid receptor nuclear hormone receptors [19]. In previous studies, retinoids increased the hepatic production of VLDL [20] and elevated the levels of apolipoprotein (apo) C-III [21], a hepatic protein that delays (1) the catabolism of VLDL particles by inhibiting their binding to the endothelial surface and (2) lipolysis by lipoprotein lipase [22].…”
Section: Discussionmentioning
confidence: 99%
“…Retinoids can stimulate phosphoenolpyruvate carboxykinase expression in the liver and hepatic gluconeogenesis. In addition, retinol is a precursor for the synthesis of ligands of the retinoic acid receptor (RAR) and retinoid X receptor (RXR) nuclear receptors; 125,126 these are partners of the peroxisome proliferator-activated receptor family that regulate genes central to fatty acid metabolism. 127 RBP4 could thus be linked to insulin resistance through impaired fatty acid metabolism, 128 and expression of several retinoidresponsive genesFRAR 2, stearoyl-CoA desaturase-1 and acetyl CoA carboxylaseFis increased in the muscle of RBP4-Tg mice.…”
Section: Retinol-binding Proteinmentioning
confidence: 99%